OBJEKTIFITAS DAN RASIONALITAS PENAFSIRAN AL-QUR’AN: PERSPEKTIF AL-JĀBIRĪ - Affandi, Abdullah (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
QurÃ¢â‚¬â„¢anic Studies had been developed according to the changing times. Scholars have offered many differentÃ‚Â methods to reveal GodÃ¢â‚¬â„¢s messages in the QurÃ¢â‚¬â„¢an. Different methods and approaches were used by a number ofleading scholars. Ã¢â‚¬ËœÃ„â‚¬bid al-JÃ„ÂbirÃ„Â« is among those leading scholars who focus on this study. In his works of MadkhalÃ‚Â ilÃ„Â al-QurÃ¢â‚¬â„¢Ã„Ân and Fahm al-QurÃ¢â‚¬â„¢Ã„Ân, al-JÃ„ÂbirÃ„Â« cultivates historically the QurÃ¢â‚¬â„¢anic discourse and interpretationÃ‚Â and suggests a new method of understanding the QurÃ¢â‚¬â„¢an. Using a philosophical-historical approach, this paperÃ‚Â examines the fundamental ideas of al-JÃ„ÂbirÃ„Â« in the QurÃ¢â‚¬â„¢anic discourse and in interpretation methodology.Keywords: Objektifikasi, Rasionalisasi, Tafsir al-QurÃ¢â‚¬â„¢an